Thermodynamic and exergoeconomic analysis of two novel tri-generation cycles for power, hydrogen and freshwater production from geothermal energy. (15th December 2020) - Abdolalipouradl, Mehran; Mohammadkhani, Farzad; Khalilarya, Shahram; Yari, Mortaza
Highlights: Two novel geothermal energy-based tri-generation cycles are proposed. The cycles generate power and produce hydrogen and freshwater. Thermodynamic and exergoeconomic analyses are carried out. The tri-generation system based on the double flash has better performance. Multi-objective optimal design results in the most promising condition. Abstract: Thermodynamic and exergoeconomic analysis of two novel tri-generation systems based on single and double flash are reported to generate power and produce hydrogen and freshwater from geothermal energy. Both proposed cycles use the organic Rankine cycle to generate power, proton exchange membrane electrolyzer to produce hydrogen and reverse osmosis desalination to produce freshwater. The proposed cycles are assessed based on the thermodynamic and exergoeconomic approaches. Different single-objective optimizations are done to maximize produced power and thermal and exergy efficiencies as well as minimize power production cost. Multi-objective optimization is also performed based on weight coefficients. Moreover, the thermodynamic and exergoeconomic parameters of the proposed systems in different conditions are investigated through a comprehensive parametric study. The results showed that the tri-generation system based on the double flash (system 2) has better performance from the exergy and exergoeconomic viewpoints compared to the single flash-based one (system 1) so that the optimum values of 8613 kW, 2.308 kg/hr, 9.502 kg/s, 12.96%, 53.79%, and 5.845 $/GJ are obtained for net power output, hydrogen production rate, desalinated water rate, energy and exergy efficiencies, and power specific cost of this system at the geofluid temperature of 200 ℃.